2021
DOI: 10.1016/j.asmr.2021.07.019
|View full text |Cite
|
Sign up to set email alerts
|

The American Shoulder and Elbow Score Is Highly Correlated With the Western Ontario Rotator Cuff Index and Has Less Responder and Administrator Burden

Abstract: Purpose To compare the correlation, responsiveness, and responder and administrator burdens of the American Shoulder and Elbow Score (ASES) with the Western Ontario Rotator Cuff Index (WORC) for patients undergoing arthroscopic rotator cuff repair to determine whether one score is superior to the other to limit the use of multiple scoring measures when tracking patient outcomes. Methods A retrospective review of a database of patients undergoing arthroscopic rotator cuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…These are the second and third most used scales in the main scientific publications. 23 The ASES scale is highly correlated with the WORC and has less responder and administrator burden, 2 which at least partially supports the scale used as the main outcome in our study.…”
Section: Discussionsupporting
confidence: 77%
“…These are the second and third most used scales in the main scientific publications. 23 The ASES scale is highly correlated with the WORC and has less responder and administrator burden, 2 which at least partially supports the scale used as the main outcome in our study.…”
Section: Discussionsupporting
confidence: 77%
“…Its superiority over other specific patient self-reported outcome measurement tools in detecting changes in clinical status after ARCR and shoulder arthroplasty has been demonstrated in previous research studies. 46,47 In our study, patients with lower ASES scores are more prone to chronic pain, and their post-surgery shoulder function recovery is considerably less compared to patients with higher ASES scores before undergoing surgery. Previous studies have shown that preoperative pain related status measured using the patient self-reported outcome assessment tool can predict the pain intensity of patients after surgery.…”
mentioning
confidence: 61%